DETERMINANTS OF HALAL MEAT CONSUMPTION AMONG INDONESIAN GENERATION Z MUSLIMS: USING THE EXTENDED THEORY OF PLANNED BEHAVIOR - Bawono, Anton; Mustofa, Nur Huri (e-Journal Ekonomi Bisnis dan Akuntansi, 2024)
This study aims to examine the factors that influence halal meat consumption intention in generation Z Indonesian Muslims, using the Theory of Planned Behavior. This research is a quantitative study using primary data, obtained through distributing questionnaires. The sample used was 1182 people who belonged to generation Z Muslims, namely the age group with the criteria: born after 1996, aged at least 15 years, had consumed certified halal meat and lived in the territory of Indonesia. This study uses Structural Equation Modeling (SEM-PLS), to test the relationship between variables in the model. The results showed that there are 5 variables that directly affect Halal Meat Consumption Intent (IKDH), namely: attitude (Att), Trust (Kep), Moral Obligation (KM), Subjective Norm (SN), and Perceive Behavioral Control (PBC). Meanwhile, there are 6 interactions that affect indirectly.